Malignant lymphomas observed in dogs in Recife - Cavalcanti, Maria Ignez; Lira, Vital (Pesquisa Agropecuaria Brasileira, 2014)
Nine case of malignant lymphomas in dogs, seven of which were among 369 post-mortem examinations, and the two others among 57 biopsies were reported. The animals were on the average 7 to 8 years old. The course of the illness averaged seven months. The lymphnode chains affected, in order of occurrence, were those of the head and neck, the mesentery, the femoral, the limb and the nodes of the mediastinum and retro-mammary regions. In the order of frequency, the involved organs were spleen, liver, Kidneys, heart, lungs, intestine and bladder. Sex and age incidences are also discussed.